(untitled) (Research, Society and Development, 2023)
Management of impacted teeth other than third molars is one of the most challenging and complicated types of dentoalveolar surgery. Proper diagnosis and treatment planning require interdisciplinary care by an orthodontist, general dentist, and oral and maxillofacial surgeon. The most common impacted teeth, other than the third molar, are the maxillary canines, maxillary second molar, mandibular second premolars, and mandibular second molar. There are systemic and local factors that contribute to the impaction of these permanent teeth. Surgical exposure of these impacted teeth is performed using several approaches. We discuss the surgical techniques used to expose the impacted canine, premolar, and second molar. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were included between the years 2000 and 2022. Treatment planning in these cases should be multidisciplinary, with the oral and maxillofacial surgeon making the final decision on the surgical treatment plan. The risk-benefit ratio generally favors preservation of the impacted tooth. In general, the recommendation is surgical exposure of the impacted tooth with orthodontic alignment in the arch. It is also recommended to upright the second molar with the removal of the impacted third molar. Close monitoring by the orthodontist and surgeon is important for the success of these procedures. Preserving these teeth is an important standard of orthodontic care.